Optimasi Efisiensi Mesin Corrugator C101: Analisis Root Cause dan FMEA untuk Meminimalisir Shortage Produksi - Wawan Gunawan; Sri Mukti Wirawati; Rico (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2026)
Production shortages are one of the main problems that impact a company's operational efficiency. This study aims to identify the factors causing production shortages in the carton sheet production process at a paper company, as well as to determine the root causes and prioritize solutions through the Root Cause Analysis (RCA) and Failure Mode and Effect Analysis (FMEA) methods. Data collection was conducted through interviews, observations, and questionnaires with Section Heads and Shift Leaders in the Corrugator C101 area. The RCA results indicate that the main causes come from machine, human, material, and method factors. Furthermore, through the FMEA method, it was found that the cause with the highest Risk Priority Number (RPN) value was shaft wear on shaft 2 with an RPN value of 179.2. The proposed solution was formulated using the 5W + 1H approach as the basis for the improvement plan. This study is expected to be a reference in strategic decision-making to minimize the risk of shortages and increase company productivity.